2020
DOI: 10.1159/000506826
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Stenosis Is Associated with Better Intracranial Collateral Circulation in Stroke Patients

Abstract: Background: Adequate collateral circulation improves the clinical outcome of ischemic stroke patients. We evaluated the influence of ipsilateral carotid stenosis on intracranial collateral circulation in acute stroke patients. Methods: We collected the data of 385 consecutive acute stroke patients who underwent mechanical thrombectomy after multimodal computed tomography (CT) imaging in a single high-volume stroke center. Patients with occlusion of the first segment (M1) segment of the middle cerebral artery w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…In the latter study, only a small number of patients with LVO were included and only those with an M1 occlusion were selected for the analysis. Nevertheless, considering recent findings in other studies [7][8][9][10], the association we describe here seems more plausible. Furthermore, intimal ICAC is related to atherosclerotic changes with the presence of plaques and arterial stenosis whereas medial ICAC is considered non-atherosclerotic without compromising the vessel lumen [1,2].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In the latter study, only a small number of patients with LVO were included and only those with an M1 occlusion were selected for the analysis. Nevertheless, considering recent findings in other studies [7][8][9][10], the association we describe here seems more plausible. Furthermore, intimal ICAC is related to atherosclerotic changes with the presence of plaques and arterial stenosis whereas medial ICAC is considered non-atherosclerotic without compromising the vessel lumen [1,2].…”
Section: Discussionsupporting
confidence: 70%
“…Formation and development of collaterals is generally thought to be stimulated by chronic cerebral hypoperfusion due to obstruction of antegrade blood flow [6]. Accordingly, previous studies found that patients with stenotic cervical [7][8][9] or intracranial [10] atherosclerosis have more extensive collaterals. Histopathological analyses of ICAC specimens revealed that the intimal calcification subtype is reflective of atherosclerotic disease, which is characterized by formation of plaques and narrowing of the vessel lumen.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al measured the direction of the ophthalmic artery flow and bilaterally in the internal carotid arteries in a group of 116 patients with unilateral carotid artery stenosis and found that the direction was reversed in 36% of the patients [33]. In another study, Pienimaki et al observed that patients with severe carotid stenosis were four times more likely to develop collateral circulation than patients with nonstenosis and moderate stenosis [34]. In our study, we established the presence of collateral circulation in 44% of patients with unilateral severe carotid artery stenosis or occlusion by DSA (Supplementary Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Collateral circulation could protect the brain parenchyma from ischemic damage when the normal antegrade ow is obstructed. These patients with ICAS had better collaterals than those with other stroke subtypes like embolism, presumably due to that the ICAS required a longer time for the complete occlusion of arteries, which allowed the development of adequate collaterals before the acute stroke 16 . Secondly, patients underlying ICASS had relatively lower clot burden compared with the embolism-related occlusion.…”
Section: Discussionmentioning
confidence: 96%